'From Gaza to the Streets of Britain': British social media coverage of the 2014 Israel-Gaza conflict. Issue 3 (2nd September 2017) - Groves, Adam
Abstract: Social media has removed the sense of distance between the public and an international conflict. However, there has been little attempt to look at the impact of this on a spectating society. This article addresses this inquiry with the 2014 Gaza War and British society. Drawing upon a variety of online sources, including tweets, Facebook comments/posts, images, and videos, this article demonstrates how the competing narratives of the Israeli-Palestinian conflict have intersected with both virtual and public space in Britain since 2014. Thus, this article is an interdisciplinary study that merges paradigms from social history and media studies to determine why the Israeli-Palestinian conflict has become an increasingly impassioned issue within Britain in recent years.